2023
DOI: 10.3390/ani13162674
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Dobutamine, Norepinephrine, Vasopressin, and Hetastarch for the Treatment of Isoflurane-Induced Hypotension in Healthy, Normovolemic Dogs

Natalia Henao-Guerrero,
Carolina H. Ricco-Pereira,
Vaidehi V. Paranjape

Abstract: Isoflurane is a commonly used inhalation anesthetic in species undergoing veterinary care that induces hypotension, impacting organ perfusion, making it imperative to minimize its occurrence or identify effective strategies for treating it. This study evaluated and compared the hemodynamic effects of DOB, NEP, VAS, and HES in twelve isoflurane-anesthetized Beagle dogs. The order of the first three treatments was randomized. HES was administered last. Data were collected before treatments (baseline) and after 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 53 publications
0
18
0
1
Order By: Relevance
“…Furthermore, some studies documented a decline in SVR in response to high volume crystalloid fluid therapy further exacerbating anaesthetic induced reductions in SVR and hypotension. 16,24,27 Large volumes of fluids may also dilute circulating red blood cells thus inhibiting increased oxygen delivery (DO 2 ) despite increased CO. 16,21,24 The majority of reviewed studies evaluated pharmacological interventions aimed at increasing blood pressure (Table 5). Dopamine infusions consistently increased blood pressure in all studies where it was used (Table 4 -Studies 2, 3, 4, 5, 9 and 11).…”
Section: Critical Appraisal Of the Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some studies documented a decline in SVR in response to high volume crystalloid fluid therapy further exacerbating anaesthetic induced reductions in SVR and hypotension. 16,24,27 Large volumes of fluids may also dilute circulating red blood cells thus inhibiting increased oxygen delivery (DO 2 ) despite increased CO. 16,21,24 The majority of reviewed studies evaluated pharmacological interventions aimed at increasing blood pressure (Table 5). Dopamine infusions consistently increased blood pressure in all studies where it was used (Table 4 -Studies 2, 3, 4, 5, 9 and 11).…”
Section: Critical Appraisal Of the Evidencementioning
confidence: 99%
“…34 Unlike the some of the studies evaluating dopamine neither noradrenaline study reported UoP or other renal parameters preventing any comparison of the renal effects of these two drugs. 13,27 Currently there are no studies directly comparing noradrenaline and dopamine for treating hypotension in dogs. Consequently, it is not possible to conclude if the two treatments are equivalent in terms of renal effects, efficacy for correcting hypotension or relevant outcomes such as survival or duration of hospitalisation.…”
Section: Critical Appraisal Of the Evidencementioning
confidence: 99%
“…The length of hospitalization between the two groups was not statistically different: 7 (4-10) days in the DEX group vs. 7 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) days in the NaCl group (p = 0.14).…”
Section: Dexmentioning
confidence: 82%
“…Considering a mean dosage of norepinephrine of 0.44 ± 0.19 mcg/kg/h [ 13 ] with an α error of 0.05 and β error of 0.2, in order to assess a decrease of 40% in the mean dosage of norepinephrine for the DEX group, a minimum requirement of 8 dogs in each group was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…El sevoflurano e isoflurano son anestésicos inhalatorios ampliamente utilizados en medicina veterinaria para la anestesia general Henao-Guerrero et al (2023). El isoflurano, en particular, exhibe una capacidad hipotensora dosis-dependiente al provocar la dilatación de los vasos periféricos y la depresión del miocardio (Kojima et al, 2021).…”
Section: Discussionunclassified